PENGARUH PIJAT BAYI TERHAOAP PENINGKATAN BERAT BAOAN BAYI USIA 3-5 BULAN 01 BIOAN PRAKTEK MANDIRI (BPM) KABUPATEN MAGETAN - Tinuk Esti Handayani; Agung Suharto; N Surtinah (JURNAL PENELITIAN KESEHATAN, 2015)
Massageis a tactile stimulation which gives the effect of biochemical and physiological effects on variousorgans of the body. The massage is done correctly and regularly in infants suspected of having variousadvantages in the process of growth and development of infants (Rosalina, 2007: 23). Objective: to knowthe baby massageincreasesweight gain in infants aged 3-5 months in BPMMagetan.The study design quasy Experimental Design, Non-equivalent control group design. Population: all infantsaged 3-5 months in BPMMagetan, with the total population. Number of samples: 50 infants were dividedinto 2 groups, massaged and massaged. Independent variables: infant massage and the dependentvariable is the baby weight. Independent Statistical Analysis Samplet T-Test and linear regression withprobability 0.05.The age of the respondent group most 4 months of treatment 17 (68%) and the control group mostlyaged 4 months 13 (52%). The mean weight of infants aged 3-5 months treatment group before and after5.720: 6.570, whereas in the control group before: 6.180 and after: 6.420. An increase in the averageweight of infants aged 3-5 months before and after the treatment group and the control group, thetreatment group increases more than the control group. Statistical analysis Independent T Test, obtainedp = 0.00 «0.05); No differences in body weight of infants aged 3-5 months treatment group and thecontrol group. Linear regression test results obtained p = 0.00 «0.05); No effect of infant massage onbody weight infants aged 3-5 months.No effect of infant massage on body weight infants aged 3-5 months in BPM Magetan. Suggestion:expected for the community to continue the routine infant massage to infants aged 2 years, as babymassaqe proved to give good effects for infant growth and also can keep the baby's immune system.Key words: baby massage,Weight